PHYSICAL – PETROGRAPHIC PARAMETERS OF COLLECTORS OF OIL AND GAS DEPOSITS OF THE CARPATHIANS NAFTOGAZONOSNOGO REGION - Грицишин, Василь Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The question of study of physical-petrography parameters of breeds-collectors of deposits Palaeogene of the Borislavsk-Pocutsk area (south-east part) of the Pre-Carpathians bending with the use of data of kern, selected in mining holes during the boring drilling, results of test of oil and gas objects taking into account the results of geophysical researches of mining holes, is examined. Confronted data of litologo-petrofizichnih properties of breeds with geological-geophysical parameters, that allowed to divide sandstones and alevroliti on two categories: industrial collectors (group And) and non-commercial (group). Ill.14. Bibl.19.